Evaluation of the prognostic value of computed tomography‐derived body composition in patients undergoing endovascular aneurysm repair - Nicholas A. Bradley; Amy Walter; Ross Dolan; Alasdair Wilson; Tamim Siddiqui; Campbell S.D. Roxburgh; Donald C. McMillan; Graeme J.K. Guthrie (Wiley, 2023)
Abstract Background Endovascular aneurysm repair (EVAR) is the most common mode of repair of abdominal aortic aneurysms (AAA) in the UK. EVAR ranges from standard infrarenal repair to complex fenestrated and branched EVAR (F/B‐EVAR). Sarcopenia is defined by lower muscle mass and function, which is associated with inferior perioperative outcomes. Computed tomography‐derived body composition analysis offers prognostic value in patients with cancer. Several authors have evaluated the role of body composition analysis in predicting outcomes in patients undergoing EVAR; however, the evidence base is limited by heterogeneous methodology. Methods Six hundred seventy‐four consecutive patients (58 (8.6%) female, mean (SD) age 74.4 (6.8) years) undergoing EVAR and F/B‐EVAR at three large tertiary centres were retrospectively recruited. Subcutaneous and visceral fat indices (SFI and VFI), psoas and skeletal muscle indices, and skeletal muscle density were measured at the L3 vertebral level from pre‐operative computed tomographies. The maximally selected rank statistic technique was used to define optimal thresholds to predict mortality. Results There were 191 deaths during the median follow‐up period of 60.0 months. Mean (95% CI) survival in the low SMI versus high SMI subgroups was 62.6 (58.5-66.7) versus 82.0 (78.7-85.3) months (P < 0.001). Mean (95% CI) survival in the low SFI versus high SFI subgroups was 56.4 (48.2-64.7) versus 77.1 (74.2-80.1) months (P < 0.001). One‐year mortality in the low SMI versus high SMI subgroups was 10% versus 3% (P < 0.001). Low SMI was associated with increased odds of one‐year mortality (OR 3.19, 95% CI 1.60-6.34, P < 0.001). Five‐year mortality in the low SMI versus high SMI subgroups was 55% versus 28% (P < 0.001). Low SMI was associated with increased odds of five‐year mortality (OR 1.54, 95% CI 1.11-2.14, P < 0.01). On multivariate analysis of all patients, low SFI (HR 1.90, 95% CI 1.30-2.76, P < 0.001) and low SMI (HR 1.88, 95% CI 1.34-2.63, P < 0.001) were associated with poorer survival. On multivariate analysis of asymptomatic AAA patients, low SFI (HR 1.54, 95% CI 1.01-2.35, P < 0.05) and low SMI (HR 1.71, 95% CI 1.20-2.42, P < 0.01) were associated with poorer survival. Conclusions Low SMI and SFI are associated with poorer long‐term survival following EVAR and F/B‐EVAR. The relationship between body composition and prognosis requires further evaluation, and external validation of the thresholds proposed in patients with AAA is required.